Permeability Properties of Concrete Using Used Motor Oil as Admixture - Sarker, Prabir; Mills, Joseph (University Publication Centre, 2009)
Huge amount of used motor oil is generated every year world wide. Used motor oil is harmful to the environment when disposed incorrectly or directly to the environment. It was shown that addition of used motor oil in a very small proportion of cement introduced entrained air in concrete. Use of air entraining agents in concrete is essential to improve its resistance against the damage caused by freezing and thawing cycles, especially in the cold climates. This paper has studied the effect of used oil on some durability properties of concrete. Used motor oil was added to 50 MPa concrete in a proportion of 0.15% by mass of the cement. This increased the air content of the fresh concrete by 65% as compared to that of the control concrete mixture. The permeability properties of hardened concrete were measured by the volume of permeable voids (VPV) test and a permeability test under a high pressure head of water. The used oil did not have any significant effect on the VPV values. Under a hydraulic head, the permeability values of the concrete specimens with used oil were higher as compared to those of the control specimens. However the values for all the specimens were within the range of average concrete. Concrete cylinders with an embedded steel bar were subjected to accelerated corrosion test under an applied voltage. No difference was observed between the times required to crack the concrete cylinders with used oil as compared to that for the control concrete.Therefore, it can be said that the resistance of the concrete against corrosion of the embedded steel bar was not reduced by the addition of used motor oil at a dosage of 0.15% by mass of the cement.